ANATOMY OF PROFESSIONAL ETHICS: DIAGNOSIS OF CRITICAL SYNDROMES AND PRESCRIPTIVE ANTIDOTES FOR NIGERIAN TEACHERS - Manga, Sani Dantani (Sokoto Educational Review, 2020)
No profession can be virile and effective without a code of ethics to guide the conduct of its practitioners. Although teacher ethics anatomically have clear prescriptive, prohibitive, legalistic and enforcement pillars, yet the fundamental principles of these ethics are neglected and violated by Nigerian teachers due to syndromes of ignorance, rigidity, ego-centricism, hedonism, and stoicism. Although the enforcement of teacher ethics may require the dispensation of punishments and rewards, yet Nigerian teachers need to look inwards and should be personally responsible for acquiring a sound knowledge of their ethics and re-awakening their conscience so as to have the intrinsic discipline of rendering altruistic service and living up to the ethical standards of their noble profession.